DETECTION OF NONTHERMAL OPTICAL FLARES FROM A BURSTER MXB 1735-44 AND X-RAY NOVA PERSEI 1992 = GRO J0422+32 - Bartolini, C.; Benvenuto, O.; Beskin, G.; Feinstein, C.; Guarnieri, A.; Meadez, M.; Mitronova, S.; Neizvestny, S.; Piccioni, A.; Plokhotnichenko, V.; Popova, M.; Zhuravkov, A. (Одеські астрономічні публікації, 2017)
During the observations on the 2.15 m telescope of CASLEO observatory (Argentina) two flares of about 0.25s duration were detected from a burster MXB 1735-44. their forward fronts had steep regions with characteristic times of 0.05 - 0.06s and thin time structure within 0.005 - 0.006s with confidence probability > 95%. Brightness temperatures of these phases of the flares, were more than 108 - 1010 K respectively. During the observations of Nova Per on the 6 m telescope of SAO stochastic flashes on a time scale from 10-20ms to 200s were recorded. The brightness temperature of the shortest flares were more than (1.7-7.0) 108 K. The events detected from these objects with high probability may be caused by nonthermal prosesses only. The rezults evidence probable departures from standard mode) of gasodynamic accretion on compact objects in MXB 1735-44 system and Nova Persei 1992.